Transverse maxillary and mandibular growth during and after Bionator therapy: study with metallic implants - André da Costa Monini; Luiz Gonzaga Gandini Júnior; Luiz Guilherme Martins Maia; Ary dos Santos-Pinto (Dental Press Editora, 2013)
INTRODUCTION: This study evaluated posteroanterior cephalograms before and after treatment and long term follow-up of Class II division 1 patients treated with bionator. OBJECTIVE: The objective was to demonstrate the transverse growth of maxilla and mandible during and after bionator therapy. METHODS: Measurement of transverse dimensions between posterior maxillary and mandibular implants, as well as the distances between the buccal, gonial and antegonial points were recorded. Measurements were analyzed at three periods: T1 = before bionator therapy, T2 = after bionator therapy and T3 = 5.74 years after T2. RESULTS: There was statistically significant transverse increase due to growth and/or treatment for all variables, except for the distance between the anterior maxillary implants. CONCLUSIONS: During the study period only the anterior maxillary area did not show transverse growth.